2018
DOI: 10.1007/s10865-018-9910-2
|View full text |Cite
|
Sign up to set email alerts
|

Public support for pictorial warnings on cigarette packs: an experimental study of US smokers

Abstract: Exposing people to a new policy through implementation could increase public support for that policy by increasing perceived effectiveness and by prompting conversations about the policy. Reactance may partially weaken the effect of policy exposure on public support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
(77 reference statements)
3
17
0
1
Order By: Relevance
“…Details of the trial including study protocols, questionnaire development, and participant recruitment have been previously published (4). Other papers using this dataset have explored the frequency and content of social interactions (36), reactance to warnings (37), and trajectories of pictorial warnings’ impact (38), as well as attitudes toward regulation of tobacco products (39, 40). From September 2014 to August 2015, we recruited English-speaking current smokers over the age of 18 to participate in the trial (see Table 1 for participant characteristics).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the trial including study protocols, questionnaire development, and participant recruitment have been previously published (4). Other papers using this dataset have explored the frequency and content of social interactions (36), reactance to warnings (37), and trajectories of pictorial warnings’ impact (38), as well as attitudes toward regulation of tobacco products (39, 40). From September 2014 to August 2015, we recruited English-speaking current smokers over the age of 18 to participate in the trial (see Table 1 for participant characteristics).…”
Section: Methodsmentioning
confidence: 99%
“…The theory emphasizes that nudges are not mandatory, and their intervention design must be simple and inexpensive [80]. It was explored in previous studies that this theory had a positive impact on several behaviors, such as reducing tobacco use [81], changing adult dietary choices [82], and increasing physical activity [83]. For medication reminders, any intervention that directly asks participants about trial content should be excluded, as this would bias the participants.…”
Section: Discussionmentioning
confidence: 99%
“…If policy influencers are taking a risk and looking to enact policy where public support is weaker, existing support is not always required prior to behaviour change, since support has been shown to increase over time following the enact ment of legislation. 14,23 Members of the general public in Alberta and Quebec had comparable levels of sup port for the majority of policy options (11/13). This finding is surprising, as pre vious research has shown that smokers in Quebec in particular had stronger support for tobacco control policies than their counterparts in Alberta.…”
Section: Guide Choices Through Changing the Default Policymentioning
confidence: 99%
“…12 Internation ally, recent research has explored public support for specific types of tobacco con trol interventions (i.e. antismoking media campaigns 13 and pictorial warnings on cigarette packs 14 in the United States of America); and support for tobacco control policies among specific population groups (i.e. smokers in Canada, 15 adolescents in Hong Kong 11 and adults in the USA, 16 Finland 17 and Malaysia 18 ).…”
mentioning
confidence: 99%